The relationship between hematological parameters and coronary angiographic lesions - Thadzia Maria de Brito Ramos; José Gildo de Moura Monteiro Júnior; Veridiana Câmara Furtado; Dário Celestino Sobral Filho (Frontiers in Cardiovascular Medicine)
Atherosclerosis is the most important etiology of acute myocardial infarction, which is considered an inflammatory disease with specific cellular and molecular responses. Recent research has linked hematological variables as biomarkers of the severity of coronary artery disease. Studies suggest that nucleated red blood cells (NRBCs), neutrophil to lymphocyte ratio (NLR), and mean platelet volume (MPV) may serve as components of a laboratory model or hematological scoring system for in-hospital surveillance. Atherosclerotic plaques can be graded using scoring systems, such as the SYNTAX score which is used to evaluate the complexity of coronary artery disease. However, there is an open field for research to explain the complex inflammatory mechanism of these plaques. Research has shown that inflammatory processes, such as those seen in coronary atherosclerotic disease, stimulate the bone marrow to release young and immature cells into the systemic circulation, which actively aggregate and, consequently, form thrombotic plaques. This mini review article aims to demonstrate the relationship between hematological parameters and coronary angiographic findings as potential in-hospital prognostic tools for patients with acute myocardial infarction. This expressive relationship between these hematological biomarkers and coronary atherosclerotic plaques may be a target, in addition to prognostic scores, of future therapeutic interventions.